Electrode film, electrode including the same, secondary battery including the same, and method for manufacturing the same
By using a high-fibrotic electrode film formed by using heat treatment and kneading processes in the lithium secondary battery electrode, the problem of low mechanical strength of the electrode is solved, and efficient manufacturing and stability improvement of the lithium secondary battery electrode is achieved.
Patent Information
- Application Number
- CN202380035101.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-20
- Filing Date
- 2023-04-20
- Publication Date
- 2024-12-13
AI Technical Summary
The existing lithium secondary battery electrodes are prone to pinholes or cracks during the drying process, resulting in a decrease in mechanical strength. The drying equipment of the existing solutions is high and is not conducive to manufacturing processability.
Using a combination of fluorine-containing adhesives such as polytetrafluoroethylene (PTFE) and lithium transition metal oxides, a high fibrous electrode film is formed through heat treatment and kneading processes to improve the elongation of breakage and tensile strength of the electrode film. .
The mechanical properties and productivity of the electrode film are significantly improved, the cost and complexity of electrode manufacturing are reduced, the solvent drying step is avoided, and the stability and processability of the electrode are enhanced.
Smart Images

Figure CN119137764A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrode film, an electrode including the same, a secondary battery, and a method for manufacturing the same. Specifically, the present disclosure relates to an electrode film having improved mechanical properties, an electrode including the same, a secondary battery, and a method for manufacturing the same.
[0002] This application claims the priority of Korean Patent Application No. 10-2022-0049211 filed in Korea on April 20, 2022, the disclosure of which is incorporated herein by reference. Background Art
[0003] As the use of fossil fuels has increased rapidly, the demand for alternative and clean energy has also increased. As part of an attempt to meet this demand, the most active area of research is the field of power generation and storage using electrochemistry. At present, typical examples of electrochemical devices that utilize electrochemical energy include secondary batteries, and their application range is also gradually expanding. As a representative of such secondary batteries, lithium secondary batteries have been used in recent years not only as an energy source for mobile instruments, but also as a power source for electric vehicles and hybrid vehicles, which can replace vehicles such as gasoline vehicles and diesel vehicles that use fossil fuels and are considered to be one of the main causes of air pollution. In addition, such lithium secondary batteries have even expanded into auxiliary power sources for electricity by forming a grid.
[0004] The process of manufacturing such a lithium secondary battery is roughly divided into the following three steps: an electrode forming step, an electrode assembly forming step, and an aging step. The electrode forming step is further divided into an electrode mixture mixing step, an electrode coating step, a drying step, a pressing step, a slitting step, a winding step, or the like.
[0005] Among these steps, the electrode mixture mixing step is a step of mixing the components for forming an electrode active layer that actually performs an electrochemical reaction in the electrode. Specifically, the electrode active material as the basic element of the electrode is mixed with other additives, a binder, a solvent, etc. to prepare a slurry with fluidity, the additives including a conductive material and a filler, the binder for bonding between powder particles and for adhesion to a current collector, and the solvent for imparting viscosity and dispersing the powder.
[0006] Then, an electrode coating step of coating the slurry onto a current collector having conductivity and a drying step of removing a solvent contained in the electrode mixture are performed, and then the resulting electrode is pressed to a predetermined thickness.
[0007] Meanwhile, as the solvent contained in the electrode mixture evaporates during the drying step, defects such as pinholes or cracks are generated in the initially formed electrode active layer. In addition, due to the different evaporation rates of the solvent, the active layer is not dried uniformly at its inside and outside, so that powder floating phenomenon occurs. In other words, the powder present in the earlier dried part will float up and form a gap with the relatively later dried part, resulting in a decrease in electrode quality.
[0008] Therefore, in order to solve the above problems, a drying device that can uniformly dry the inside and outside of the active layer and control the evaporation rate of the solvent has been considered. However, this drying device is expensive, requires a lot of cost and time to operate, and is therefore disadvantageous in terms of manufacturing processability.
[0009] Therefore, active research has recently been conducted to fabricate dry electrodes without using any solvent.
[0010] A method for manufacturing a dry electrode includes the following steps: subjecting a mixture of a fiberizable binder (such as polytetrafluoroethylene (PTFE)), an active material, and a conductive material to a roll-calendering process to obtain a free-standing electrode film. However, when the mechanical strength of the electrode film is reduced, it may become a cause of defects in subsequent processes for manufacturing the electrode. Summary of the invention
[0011] Technical issues
[0012] The present disclosure is designed to solve the problems of the prior art, and thus the present disclosure aims to provide an electrode film having improved mechanical properties, an electrode and a secondary battery including the electrode film, and a method of manufacturing the same.
[0013] Technical Solution
[0014] In one aspect of the present disclosure, an electrode according to any one of the following embodiments is provided.
[0015] According to a first embodiment of the present disclosure, an electrode film is provided, comprising: an active material and a fluorine-containing adhesive, wherein the fluorine-containing adhesive comprises a polytetrafluoroethylene (PTFE) adhesive, the active material comprises a lithium transition metal oxide, and based on 100 parts by weight of the total weight of the electrode film, the content of the fluorine-containing adhesive is 0.5-10 parts by weight, and the electrode film exhibits an elongation at break of more than 7%.
[0016] According to a second embodiment of the present disclosure, there is provided an electrode film as defined in the first embodiment, wherein the lithium transition metal oxide includes lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel-manganese-cobalt oxide, lithium nickel-manganese-cobalt-aluminum oxide, lithium copper oxide, or two or more of them.
[0017] According to a third embodiment of the present disclosure, there is provided an electrode film as defined in the second embodiment, wherein the lithium nickel-manganese-cobalt-aluminum oxide is represented by the following Chemical Formula 1:
[0018] [Chemical Formula 1]
[0019] Li a [Ni b Co c Mn d Al e 1-f M 1 f O2
[0020] wherein M l represents Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, S, or two or more of them, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, and 0 ≤ f ≤ 0.1.
[0021] According to a fourth embodiment of the present disclosure, there is provided an electrode film as defined in the second embodiment or the third embodiment, wherein the lithium nickel-manganese-cobalt-aluminum oxide is represented by the following Chemical Formula 2:
[0022] [Chemical Formula 2]
[0023] Li a [Ni b Co c Mn d Al e 1-f O2
[0024] wherein 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1 and 0 ≤ f ≤ 0.1.
[0025] According to a fifth embodiment of the present disclosure, there is provided an electrode film as defined in any one of the first embodiment to the fourth embodiment, the electrode film showing an elongation at break of more than 7% and a tensile strength of more than 1.4 MPa.
[0026] According to a sixth embodiment of the present disclosure, there is provided an electrode film as defined in the fifth embodiment, the electrode film exhibiting an elongation at break of 7.2-7.8%, a tensile strength of 1.4 MPa, and a modulus of 38.3-40.9 MPa.
[0027] According to a seventh embodiment of the present disclosure, there is provided an electrode film as defined in any one of the first to sixth embodiments, including an active material, a fluorine-containing binder, and a conductive material.
[0028] According to an eighth embodiment of the present disclosure, there is provided an electrode film as defined in the seventh embodiment, wherein the conductive material includes activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more thereof.
[0029] According to a ninth embodiment of the present disclosure, there is provided an electrode film as defined in the seventh embodiment or the eighth embodiment, wherein the content of the active material is 85-98 parts by weight, the content of the conductive material is 0.5-5 parts by weight, and the content of the fluorine-containing binder is 0.5-10 parts by weight.
[0030] According to a tenth embodiment of the present disclosure, there is provided an electrode film as defined in any one of the first to ninth embodiments, the electrode film being obtained by a dry process.
[0031] According to an eleventh embodiment of the present disclosure, there is provided a method for manufacturing an electrode film as defined in any one of the first to tenth embodiments, comprising the following steps:
[0032] The fluorine-containing adhesive is heat treated at 290-310°C;
[0033] preparing a mixture comprising an active material and the heat-treated fluorine-containing binder;
[0034] kneading the mixture at a pressure equal to or higher than ambient pressure at 70-200° C. to prepare a mixture mass;
[0035] pulverizing the mixture mass to obtain a mixed powder for an electrode; and
[0036] The electrode mixed powder is introduced between a plurality of rolls and rolled to form an electrode film.
[0037] According to a twelfth embodiment of the present disclosure, there is provided a method for manufacturing an electrode film as defined in the eleventh embodiment, wherein the step of kneading the mixture to prepare a mixture mass is performed in a kneader at a pressure equal to or higher than ambient pressure.
[0038] According to a thirteenth embodiment of the present disclosure, there is provided a method for manufacturing an electrode including the step of laminating the electrode film as defined in any one of the first to tenth embodiments on a current collector.
[0039] According to a fourteenth embodiment of the present disclosure, there is provided a method for manufacturing an electrode as defined in the thirteenth embodiment, wherein in the laminating step, the electrode film has a compression ratio of 30-50%.
[0040] According to a fifteenth embodiment of the present disclosure, there is provided an electrode including: a current collector; and the electrode film as defined in any one of the first to tenth embodiments provided on at least one surface of the current collector.
[0041] According to a sixteenth embodiment of the present disclosure, there is provided an electrode as defined in the fifteenth embodiment, wherein the current collector further includes a conductive primer layer on at least one surface thereof.
[0042] According to a seventeenth embodiment of the present disclosure, there is provided a secondary battery including: a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is the electrode as defined in the fifteenth or sixteenth embodiment.
[0043] According to an eighteenth embodiment of the present disclosure, there is provided an energy storage system including the secondary battery as defined in the seventeenth embodiment as a unit battery.
[0044] Beneficial Effects
[0045] According to an embodiment of the present disclosure, an electrode membrane is obtained by heat-treating a fluorine-containing adhesive at 290-310° C. and mixing the heat-treated adhesive with an active material, etc. Here, when the fluorine-containing adhesive is preliminarily heat-treated, the bonding between the primary particles in the secondary particles of the fluorine-containing adhesive (such as PTFE) is improved by means of melt inter-diffusion on the surface between the adhesive particles, thereby facilitating the fibrilization of the fluorine-containing adhesive in the subsequent electrode membrane manufacturing process. As a result, the electrode membrane includes a fluorine-containing adhesive, which has a higher degree of fibrilization than a conventional electrode membrane, and thus shows significantly improved mechanical properties and increased membrane productivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the foregoing disclosure, are used to provide a further understanding of the technical features of the present disclosure. Therefore, the present disclosure should not be construed as being limited to the accompanying drawings.
[0047] Figure 1 is a schematic diagram illustrating a process for manufacturing an electrode film according to an embodiment of the present disclosure.
[0048] Figure 2 is a schematic diagram illustrating an electrode lamination step according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0049] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings.
[0050] Prior to the description, it should be understood that the terms used in the specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted based on the meaning and concept of the technical aspects corresponding to the present disclosure on the basis of the principle allowing the inventor to appropriately define the terms for the best interpretation.
[0051] The terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the present disclosure.As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0052] It should be further understood that when the terms “include” and / or “comprising” or “include” and / or “including” are used in this specification, they do not exclude the existence of other elements, but specify the additional existence of other elements, unless otherwise specified.
[0053] In one aspect of the present disclosure, an electrode film is provided, comprising: an active material and a fluorine-containing adhesive, wherein the fluorine-containing adhesive comprises a polytetrafluoroethylene (PTFE) adhesive, the active material comprises a lithium transition metal oxide, and based on 100 parts by weight of the total weight of the electrode film, the content of the fluorine-containing adhesive is 0.5-10 parts by weight, and the electrode film exhibits an elongation at break of more than 7%.
[0054] The active material includes a lithium transition metal oxide.
[0055] According to an embodiment of the present disclosure, the lithium transition metal oxide may include lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel-manganese-cobalt oxide, lithium nickel-manganese-cobalt-aluminum oxide, lithium copper oxide, or two or more thereof.
[0056] Specific examples of the lithium transition metal oxide include: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or those compounds substituted with one or more transition metals; lithium manganese oxides such as those represented by the chemical formula Li 1+x Mn 2-x O4 (where x is 0 - 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); Ni-site lithium nickel oxides represented by the chemical formula LiNi 1-x M x O2 (where M is Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and x is 0.01 - 0.3); lithium manganese composite oxides represented by the chemical formula LiMn 2-x M x O2 (where M is Co, Ni, Fe, Cr, Zn, or Ta, and x is 0.01 - 0.1) or Li2Mn3MO8 (where M is Fe, Co, Ni, Cu, or Zn); lithium nickel - manganese - cobalt - aluminum oxides represented by Chemical Formula 1; or the like.
[0057] [Chemical Formula 1]
[0058] Li a [Ni b Co c Mn d Al e 1-f M 1 f O2
[0059] where M l represents Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, S, or two or more of them, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, and 0 ≤ f ≤ 0.1.
[0060] According to an embodiment of the present disclosure, the lithium nickel - manganese - cobalt - aluminum oxide can be represented by the following Chemical Formula 2:
[0061] [Chemical Formula 2]
[0062] Li a [Ni b Co c Mn d Al e 1-f O2
[0063] Where 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1 and 0 ≤ f ≤ 0.1.
[0064] Specifically, the lithium nickel-manganese-cobalt-aluminum oxide may include Li[Ni 0.73 Co 0.05 Mn 0.15 Al 0.02 O2) or the like.
[0065] According to an embodiment of the present disclosure, the electrode film may include an active material, a fluorine-containing binder, and a conductive material.
[0066] The conductive material is not particularly limited as long as it has conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of the conductive material include: graphite, such as natural graphite or artificial graphite; carbonaceous materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, or carbon fiber; metal powders or metal fibers, such as copper, nickel, aluminum, or silver; needle-like or dendritic conductive whiskers, such as zinc oxide whiskers, calcium carbonate whiskers, titanium dioxide whiskers, silicon oxide whiskers, silicon carbide whiskers, aluminum borate whiskers, magnesium borate whiskers, potassium titanate whiskers, silicon nitride whiskers, silicon carbide whiskers, or aluminum oxide whiskers; conductive metal oxides, such as titanium dioxide; conductive polymers, such as polyphenylene derivatives; or the like. These conductive materials may be used alone or in combination. In particular, the conductive material may include at least one selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more particularly activated carbon, so that the conductive material is uniformly mixed and the conductivity is improved.
[0067] The fluorine-containing binder may include a fluorine-containing polymer, particularly polytetrafluoroethylene (PTFE). In addition, the fluorine-containing binder may contain polytetrafluoroethylene alone, or may further include at least one selected from polyvinylidene fluoride (PVDF) and PVDF-based copolymers (such as polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP)) in addition to polytetrafluoroethylene.
[0068] Here, the elongation at break of the electrode film refers to the elongation when the electrode film breaks. Specifically, the elongation at break of the electrode film refers to the strain when, in the process of increasing the load applied thereto to deform the length of the electrode film having a predetermined size, the film no longer deforms and breaks.
[0069] According to an embodiment of the present disclosure, the elongation at break of an electrode film may be measured using a UTM instrument (ZwickRoell Co.) under the following test conditions.
[0070] Test conditions: ASTM D 638, preload 0.01 kg / cm, test speed 50 mm / min.
[0071] Here, according to the present disclosure, the tensile strength of the electrode film refers to the maximum stress until the electrode film breaks. Specifically, the tensile strength of the electrode film refers to the value calculated by dividing the maximum tensile load by the initial cross-sectional area of the sample when the film is no longer deformed and breaks during the process of increasing the load applied thereto to deform the length of the electrode film having a predetermined size.
[0072] Modulus is a constant that represents the ratio of deformation (stress) to distortion of an elastic body, also known as elastic coefficient. When an external force is applied to an object to cause deformation, within the range where the deformation is not significant, the stress generated by the external force and the distortion generated by the deformation are proportional to each other (Hooke's law), and the proportional constant here is called modulus.
[0073] As used herein, the modulus of an electrode film refers to a proportionality constant of stress to distortion generated by deformation of the electrode film.
[0074] According to an embodiment of the present disclosure, the tensile strength and modulus of the electrode film may be measured using a UTM instrument (ZwickRoell Co.) under the following test conditions.
[0075] Test conditions: ASTM D 638, preload 0.01 kg / cm, test speed 50 mm / min.
[0076] The electrode film may exhibit an elongation at break of 7% or more. According to an embodiment of the present disclosure, the electrode film may exhibit an elongation at break of 7-10%, 7-9%, 7-8%, 7.2-7.8%, 7.2-7.4%, or 7.4-7.8%.
[0077] The electrode film may have a tensile strength of 1.1 MPa or more, or 1.1-1.4 MPa.
[0078] The electrode film may have a modulus of 32.7 MPa or greater, 32.7-40.9 MPa, or 38.3-40.9 MPa.
[0079] Based on 100 parts by weight of the total weight of the electrode film, the content of the fluorine-containing binder is 0.5-10 parts by weight. According to an embodiment of the present disclosure, based on 100 parts by weight of the total weight of the electrode film, the content of the fluorine-containing binder may be 0.5-5 parts by weight, 0.5-3 parts by weight, or 3-10 parts by weight.
[0080] When the content of the fluorine-containing binder is less than 0.5 parts by weight, the electrode film cannot be manufactured by molding the mixed powder formed through the pulverization step. When the content of the fluorine-containing binder is greater than 10 parts by weight, there is a problem that the physical properties of the film are degraded due to the non-uniformity of the mixed powder.
[0081] The electrode film may include an active material, a fluorine-containing binder, and a conductive material.
[0082] According to an embodiment of the present disclosure, the content of the active material can be 85-98 parts by weight, the content of the conductive material can be 0.5-5 parts by weight, and the content of the fluorine-containing adhesive can be 0.5-10 parts by weight. In addition, the content of the active material is 85-96 parts by weight, 90-98 parts by weight, 90-96 parts by weight, or 96-98 parts by weight, the content of the conductive material can be 0.5-5 parts by weight, 0.5-1 parts by weight, or 1-5 parts by weight, and the content of the fluorine-containing adhesive can be 0.5-5 parts by weight, 3-5 parts by weight, or 3-10 parts by weight.
[0083] When the content of active material, the content of conductive material and the content of fluorine-containing binder satisfy the above ranges, the fluorine-containing binder can be sufficiently fiberized in the subsequent kneading step to form a mixture mass, an electrode film can be easily obtained by molding the mixed powder formed by the pulverizing step, the physical properties of the electrode film can be ensured, the content of active material can be ensured to prevent the problem of capacity decrease, and sufficient conductivity can be ensured.
[0084] Meanwhile, a filler may be further introduced into the electrode layer as a component for suppressing electrode expansion as appropriate. The filler is not particularly limited as long as it is a fiber material and does not cause any chemical changes in the corresponding battery. Specific examples of the filler include: olefin polymers such as polyethylene or polypropylene; fiber materials such as glass fiber or carbon fiber; or the like.
[0085] In another aspect of the present disclosure, there is provided an electrode comprising:
[0086] Current collector; and
[0087] According to the electrode film of the embodiment of the present disclosure, the electrode film is provided on at least one surface of the current collector.
[0088] The current collector is not particularly limited as long as it has high conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of current collectors include stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel treated with carbon, nickel, titanium, silver, or the like. In addition, fine surface irregularities can be formed on the surface of the current collector to enhance the binding force with the positive electrode active material. The current collector can be used in various shapes including films, sheets, foils, nets, porous bodies, foams, nonwoven nets, or similar shapes.
[0089] In addition, the current collector can be coated with a conductive primer layer in whole or in part to reduce surface resistance and improve adhesion. Here, the conductive primer layer can include a conductive material and a binder. The conductive material is not particularly limited as long as it has conductivity. For example, the conductive material can include: a carbonaceous material, a metallic material (metal powder or metal fiber), a conductive whisker, a conductive metal oxide, a conductive polymer or the like. The carbonaceous material can include natural graphite, artificial graphite, graphene, carbon black, denka black, acetylene black, ketjen black, Super-P, channel black, furnace black, lamp black, thermal black, carbon nanotubes, graphite nanofibers, carbon nanofibers or the like. The metal material may include copper, nickel, aluminum, silver, or the like, the conductive whisker may include zinc oxide whisker, calcium carbonate whisker, titanium dioxide whisker, silicon oxide whisker, silicon carbide whisker, aluminum borate whisker, magnesium borate whisker, potassium titanate whisker, silicon nitride whisker, silicon carbide whisker, aluminum oxide whisker, or the like, the conductive metal oxide may include titanium dioxide or the like, the conductive polymer may include a polyphenylene derivative or the like. These materials may be used alone or in combination.
[0090] The adhesive may be a fluorine-based adhesive (including PVDF and PVDF copolymers) or an acrylic adhesive soluble in a solvent, and may include a water-based adhesive such as styrene butadiene rubber (SBR).
[0091] Another aspect of the present disclosure provides a method for manufacturing an electrode film according to an embodiment of the present disclosure, comprising the following steps:
[0092] The fluorine-containing adhesive is heat treated at 290-310°C;
[0093] preparing a mixture comprising an active material and the heat-treated fluorine-containing binder;
[0094] kneading the mixture at a pressure equal to or higher than ambient pressure at 70-200° C. to prepare a mixture mass;
[0095] pulverizing the mixture mass to obtain a mixed powder for an electrode; and
[0096] The electrode mixed powder is introduced between a plurality of rolls and rolled to form an electrode film.
[0097] Hereinafter, the method for manufacturing an electrode film according to the present disclosure will be explained in more detail.
[0098] First, the fluorine-containing adhesive is heat-treated at 290-310°C.
[0099] When the fluorine-containing binder is subjected to preliminary heat treatment alone before being mixed with the active material, the primary particles in the secondary particles of the fluorine-containing binder (such as PTFE) are firmly bonded to each other by melt inter-diffusion on the surface between the binder particles. As a result, the fiberization of the fluorine-containing binder can easily occur in the subsequent step of forming the electrode film.
[0100] Compared with conventional electrode membranes, electrode membranes including fluorinated binders have a higher degree of fiberization, showing significantly improved mechanical properties and increased membrane productivity.
[0101] The heat treatment of the fluorine-containing adhesive can be performed in an air atmosphere using a device such as a furnace.
[0102] The heat treatment temperature of the fluorine-containing adhesive is 290-310° C. According to an embodiment of the present disclosure, the heat treatment temperature of the fluorine-containing adhesive may be 290-300° C., 300-310° C., 292-308° C., or 293-307° C.
[0103] When the heat treatment temperature of the fluorine-containing adhesive is lower than 290° C., there is no effect of the heat treatment. When the heat treatment temperature is higher than 310° C., the sheet cannot be formed, which is disadvantageous in film processing.
[0104] Next, a mixture including an active material and a heat-treated fluorine-containing binder is prepared.
[0105] Here, the mixing for preparing the mixture is carried out in a manner that the electrode active material and the heat-treated fluorinated adhesive can be evenly distributed. In addition, since the mixture is mixed in the form of powder, any mixing method that can simply mix the components can be used without particular restrictions, and the components can be mixed by various processes. However, since the electrode film according to the present disclosure is manufactured as a dry electrode without using a dispersion medium, it can be mixed by a dry mixing process, and the components can be introduced into an instrument (such as a blender) for mixing. According to an embodiment of the present disclosure, in addition to the active material and the heat-treated fluorinated adhesive, the mixture can also be prepared by further introducing a conductive material or the like.
[0106] Furthermore, mixing may be performed in a mixer at 5,000-20,000 rpm for 30 seconds to 2 minutes, and specifically, at 10,000-15,000 rpm for 30 seconds to 1 minute to ensure uniformity.
[0107] There is no particular limitation on the fluorine-containing adhesive, as long as it can be finely fibrillated by the step of preparing the mixed powder and contains fluorine as described above. Fine fibrillation refers to the process of finely dividing the polymer, for example, it can be carried out using mechanical shear force or the like. Specific examples of fluorine-containing adhesives may include fluorine-containing polymers as described above, and specifically may include polytetrafluoroethylene (PTFE) alone or in combination with at least one PVDF-based polymer such as polyvinylidene fluoride (PVDF) or polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP).
[0108] Next, the mixture is kneaded at 70-200° C. under a pressure equal to or higher than ambient pressure to prepare a mixture mass.
[0109] According to the prior art, high shear mixing, such as jet milling, is performed to fiberize the binder. However, in this case, there is a problem that the active material is micronized by mixing and the resulting fibers may be cut. According to the present disclosure, this problem is solved by using a low shear kneading process instead of high shear mixing.
[0110] The kneading is not limited to a specific process. According to an embodiment of the present disclosure, the kneading may be performed by a kneader or the like.
[0111] The kneading step is a step of binding or connecting the active material and conductive material powder particles while the fluorine-containing binder is fiberized, thereby forming a mixture mass having a solid content of 100%.
[0112] Specifically, kneading can be controlled to a kneading rate of 10-100rpm. For example, the kneading rate can be controlled to 20-70rpm within the above range. Kneading can be carried out for 1-30 minutes. For example, kneading can be carried out for 3-10 minutes at a rate of 40-70rpm within the above-defined range. At the same time, kneading can be controlled to a shear rate of 10 / s to 500 / s. According to an embodiment of the present disclosure, kneading can be carried out for 1-30 minutes, and the shear rate can be controlled to 30 / s to 100 / s.
[0113] At the same time, the kneading step may be carried out at ambient pressure or higher pressure conditions, in particular pressure conditions higher than ambient pressure, at elevated temperature.
[0114] More specifically, kneading of the mixture may be performed at 70-200°C, specifically 90-150°C.
[0115] When kneading is performed at a low temperature exceeding the temperature range defined above, the fiberization of the fluorine-containing adhesive and the formation of agglomerates by kneading cannot be fully performed during kneading. Therefore, a film cannot be easily formed during calendering. On the other hand, when kneading is performed at an excessively high temperature, the fluorine-containing adhesive may be rapidly fiberized, and the resulting fiber may be cut by excessive shearing force, which is undesirable.
[0116] In addition, kneading can be performed at a pressure equal to or higher than ambient pressure, specifically 1-100 atm, more specifically 10-80 atm. When the above-defined pressure range is met, the problems of the resulting fibers being cut and the density of the mixture mass being excessively increased due to the application of excessive shear force and pressure can be prevented. In other words, according to the present disclosure, when a low shear mixing step is performed at a high temperature under a pressure condition equal to or higher than ambient pressure instead of high shear mixing, the desired effect can be achieved.
[0117] Then, the mixture mass is pulverized to obtain a mixed powder for an electrode.
[0118] Specifically, the mixture mass prepared by kneading can be directly subjected to calendaring. However, in this case, it is necessary to press the mixture mass to convert it into a film. As a result, there is a problem that the film may have too high a density or a uniform film cannot be obtained. Therefore, according to the present disclosure, the mixture mass is subjected to a pulverization step.
[0119] Here, the pulverizing step may be performed by using a known pulverizing instrument, such as a mixer or a grinder, but is not limited thereto. Specifically, the pulverizing step may be performed at a rate of 5,000-20,000 rpm for 30 seconds to 10 minutes, more specifically, at a rate of 10,000-18,000 rpm for 30 seconds to 2 minutes.
[0120] When the above-defined pulverization rate and time are met, pulverization can be sufficiently performed to form a powder having a size suitable for film formation and to prevent the problem of a large amount of fine powder being generated from the mixture mass. If necessary, a classification step for sieving powder having a size smaller or larger than a predetermined size can be performed.
[0121] Thereafter, the mixed powder for electrode is introduced between a plurality of rolls to be rolled, thereby forming an electrode film.
[0122] Reference Figure 1, a step 100 of forming an electrode film is shown, wherein a plurality of rollers 110 are arranged to be spaced apart from each other. The electrode mixed powder 120 obtained by the previous step is introduced between adjacent rollers 110, and the rollers 110 are rotated in opposite directions. In this way, the mixed powder 120 is pressed and then subjected to a powder tableting step, so that it can be formed into a sheet or a film. Then, multiple rolling is performed to obtain an electrode film having a final target thickness.
[0123] Specifically, the rolling includes processing the electrode mixed powder into a film shape. For example, the electrode mixed powder can be formed into a film with an average thickness of 50-300 μm.
[0124] Here, the calendering may be performed by using rolls facing each other, wherein the roll temperature may be 50-200° C. and the roll rotation speed ratio may be controlled within the range of 1.0-2.0.
[0125] After the calendaring step is completed, a dry electrode film serving as an electrode mixture can be obtained. According to the prior art, the dry electrode film can also be referred to as a free-standing film.
[0126] The obtained dry electrode film does not contain solvent and has almost no fluidity, so it can be easily handled and processed into a desired shape for manufacturing electrodes of various shapes. In addition, when the dry electrode film according to the present disclosure is used to manufacture an electrode, the drying step for removing the solvent can be omitted, so the production processability of the electrode can be significantly improved, and the problems of the method for manufacturing dry electrodes according to the prior art, such as the brittleness of the active material or the cutting of the fiberized fluorine-containing binder, can be solved.
[0127] At the same time, according to the present disclosure, the dry electrode film may have a porosity of 20-50%. Within the above-defined range, the porosity may preferably be controlled to a value of less than 40%, or less than 30%. When the porosity satisfies the above range, the wetting of the electrolyte can be promoted, thereby obtaining improvements in life characteristics, output characteristics, or the like. In addition, since the volume required to achieve the same capacity is not increased, the energy density based on volume can be improved. According to an embodiment of the present disclosure, the porosity can be obtained by determining the apparent density of the dry electrode film and using the true density calculated based on the true density of each component and composition according to the following formula:
[0128] Porosity (%) = {1-(apparent density / true density)} × 100
[0129] In still another aspect of the present disclosure, there is provided a method for manufacturing an electrode, including the step of laminating the electrode film according to the embodiment of the present disclosure on a current collector.
[0130] The lamination step may be a step of pressing and adhering the electrode film obtained by the method for manufacturing an electrode film according to an embodiment of the present disclosure to a current collector to a desired thickness. Lamination may also be performed by using a lamination roller, wherein the lamination roller may be maintained at a temperature of 25-250°C.
[0131] According to an embodiment of the present disclosure, the electrode film may have a compression ratio of 30-50%, 35-50%, or 40-50%.
[0132] The compression ratio of the electrode film may be defined as the ratio of the compressed thickness of the electrode film when laminated, and may be expressed by the following Formula 1:
[0133] [Formula 1]
[0134] Compression ratio (%) = T p / T1×100
[0135] Among them, T p represents the pressed thickness of the electrode film in the lamination step, and T1 represents the thickness of the electrode film before the lamination step.
[0136] According to the present disclosure, the lamination step can be controlled to meet a specific compression ratio. In this way, an electrode film with appropriate density and porosity can be provided, and excellent adhesion between the electrode film and the current collector can be achieved.
[0137] When the electrode film satisfies a compression ratio of 30-50%, the pressure applied to the electrode film is sufficient to improve the adhesion between the electrode film and the current collector. In addition, the problem of separation of the electrode film from the current collector after the lamination step can be prevented, and the problem of undesirable increase in the density of the electrode film, decrease in the porosity of the electrode film compared to the target porosity, or damage to the current collector can be solved.
[0138] According to an embodiment of the present disclosure, when the electrode film is laminated onto both surfaces of the current collector, the compression ratio (%) of Formula 1 may be expressed by the following Formula 2:
[0139] [Formula 2]
[0140] 30≤(T1+0.5T c -0.5T gap ) / T1×100≤50
[0141] Where T1 represents the thickness of the electrode film before the lamination step, T c represents the thickness of the current collector, and T gap Indicates the gap between the first roller and the second roller.
[0142] Furthermore, the electrode film subjected to the lamination step may have a pressing ratio of 20% or less, 18% or less, 15% or less, 5-15%, 6-15%, 7-15%, or 9-13%.
[0143] Here, the pressing ratio may be defined as a ratio of the thickness of the electrode film after the lamination step to the thickness of the electrode film before the lamination step, and may be represented by the following Formula 3:
[0144] [Formula 3]
[0145] Compression ratio (%) = (T1-T2) / T1×100
[0146] Here, T1 represents the thickness of the electrode film before the lamination step, and T2 represents the thickness of the electrode film after the lamination step.
[0147] When the pressing ratio satisfies the above range, a resulting electrode film having appropriate density and porosity may be provided, and excellent adhesion between the electrode film and the current collector may be achieved.
[0148] The increase in apparent density before and after laminating the electrode film with the current collector can be expressed by the following formula 4:
[0149] [Formula 4]
[0150] Apparent density increase (%) = (D2-D1) / D1×100
[0151] Where D1 represents the apparent density of the electrode film before the lamination step (g / cm 3 ), D2 represents the apparent density of the electrode film after the lamination step (g / cm 3 ).
[0152] Before and after lamination of the electrode film with the current collector, the apparent density of the electrode film may be increased by 5-30%, 7-25%, or 10-20%. Here, D1 and D2 may each be 2.75 g / cm 3 Up to 3.5g / cm 3 Meanwhile, when the electrode film satisfies the above-defined apparent density increase range, the adhesion between the electrode film and the current collector can be improved and the problem of the porosity exceeding the target range or causing damage to the positive electrode active material or the current collector can be prevented.
[0153] The apparent density before and after lamination of the electrode film with the current collector can be calculated by measuring the weight and thickness of the electrode film before lamination, measuring the weight and thickness of the electrode after lamination, and calculating the weight and thickness of the film minus the weight and thickness of the current collector.
[0154] In addition, the dry electrode film can have 3-15 mAh / cm 2, especially 4-10mAh / cm 2 of active material loading.
[0155] Here, the active material loading amount is a value calculated according to the following formula 5:
[0156] [Formula 5]
[0157] Active material loading (mAh / cm 2 ) = capacity of active material (mAh / g) × weight ratio of active material in dry electrode film (wt%) × unit area weight of dry electrode film (g / cm 2 )
[0158] In addition, the interfacial resistance between the dry electrode film and the current collector can be 5Ω·cm 2 Below, specifically 2Ω·cm 2 Herein, the interface resistance can be calculated by determining the resistance value between the dry electrode film and the collector layer as the potential difference measured between multiple probes after applying a current of 100 μA to the electrode by a multi-probe (MP) resistance test method. When the interface resistance satisfies the above range, the secondary battery subsequently obtained may have improved performance.
[0159] Figure 2 2 is a schematic diagram showing a step of laminating an electrode film on both surfaces of a current collector according to an embodiment of the present disclosure. In other words, in the lamination step 200, the electrode film 230 obtained by the previous step can be pressed and adhered to the current collector 220 to a desired thickness by using a pair of lamination rollers 210, thereby providing a finished electrode 240.
[0160] In another aspect of the present disclosure, a dry electrode obtained by a method for manufacturing a dry electrode is provided. A secondary battery comprising the dry electrode is also provided, wherein the dry electrode is a positive electrode, and the secondary battery comprises an electrode assembly, the electrode assembly comprising a positive electrode, a negative electrode and a separator and is contained in a battery housing (cylindrical housing, prismatic housing, bag or the like) together with a lithium-containing non-aqueous electrolyte. In addition, an energy storage system comprising the secondary battery as a unit cell is provided.
[0161] Here, since detailed structures of the secondary battery and the energy storage system are known to those skilled in the art, a detailed description thereof will be omitted in the present disclosure.
[0162] In another aspect of the present disclosure, a system for manufacturing a dry electrode film is provided. The system includes: a mixer configured to mix the components of an electrode mixture including an active material, a conductive material, and a fluorine-containing binder; a kneader configured to knead the mixture of the components to form a mixture mass; a pulverizer configured to pulverize the mixture mass to form a mixed powder for an electrode; a calender configured to form a dry electrode film from the mixed powder for an electrode; and a laminating roller configured to place the dry electrode film on at least one surface of a current collector and perform lamination.
[0163] A stirrer is a mixer configured to mix the ingredients. As described above, the ingredients of the mixture can be mixed at a rate of 5,000-20,000 rpm. A kneader is a device for fibrillating the fluorine-containing adhesive and dispersing the ingredients of the mixture according to the present disclosure, and the mixture can be obtained in the form of a mixture mass by kneading in a kneader. For this purpose, the kneader can be set to a temperature of 70-200° C. and a pressure condition equal to or higher than ambient pressure. Specifically, the kneader can be set to a temperature of 90-180° C. and a pressure condition of 1-100 atm, more specifically 10-80 atm.
[0164] The pulverizer is configured to pulverize the obtained mixture mass to form a mixed powder for an electrode, and may include a blender or a grinder.
[0165] The calender is a device for molding the mixed powder for the electrode into a film shape. For example, the calender may include a pair of rollers facing each other, and the film thickness may be controlled by the interval between the rollers.
[0166] The laminating roller serves to attach and press the dry electrode film formed by the calendaring machine onto at least one surface of the current collector.
[0167] The porosity of the dry electrode film according to the present disclosure may be determined by a calendar and a lamination roll.
[0168] In other words, the system for manufacturing a dry electrode according to the present disclosure is characterized by including a kneader and a pulverizer.
[0169] The specific structures of the mixer, kneader, calender and laminating roller are known to those skilled in the art, and a detailed description thereof will be omitted here.
[0170] Embodiments will be described more fully below so that the present disclosure can be easily understood. However, the following embodiments can be implemented in many different forms and should not be construed as being limited to the exemplary embodiments set forth therein. Rather, these exemplary embodiments are provided so that the present disclosure will be thorough and complete, and the scope of the present disclosure will be fully conveyed to those skilled in the art.
[0171] Comparative Example 1
[0172] <Manufacturing of electrode film>
[0173] First, 96 g of lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.73 Co 0.05 Mn 0.15 Al 0.02 ]O2), 1g of carbon black as a conductive material and 3g of polytetrafluoroethylene (PTFE) as a fluorine-containing binder are introduced into a blender and mixed at 50rpm for 5 minutes to prepare a mixture. The temperature of the kneader is stabilized at 150°C, the mixture is introduced into the kneader, and the kneader is operated at a rate of 50rpm for 5 minutes under a cover pressure of 1.1atm to obtain a mixture mass. The mixture mass is introduced into a blender, crushed at 10,000rpm for 1 minute, and classified by using a sieve with a hole size of 1mm to obtain a mixed powder for an electrode. Then, the obtained mixed powder for an electrode is introduced into a laboratory calender (roller diameter: 160mm, roller temperature: 100°C) to obtain an electrode film. The thickness of the obtained electrode film is 80μm.
[0174] Examples 1-3
[0175] <Manufacturing of electrode film>
[0176] An electrode film was obtained in the same manner as in Comparative Example 1, except that polytetrafluoroethylene (PTFE) as a fluorine-containing binder was heat treated in an air atmosphere using a furnace at a heat treatment temperature and for a heat treatment time as shown in Table 1 below, and then cooled to room temperature (25°C).
[0177] Comparative Examples 2 and 3
[0178] <Manufacturing of electrode film>
[0179] An electrode film was obtained in the same manner as in Comparative Example 1, except that polytetrafluoroethylene (PTFE) as a fluorine-containing binder was heat treated in an air atmosphere using a furnace at a heat treatment temperature and for a heat treatment time as shown in Table 1 below, and then cooled to room temperature (25°C).
[0180] Comparative Example 4
[0181] <Manufacturing of electrode film>
[0182] An electrode film was obtained in the same manner as in Comparative Example 1, except that 87 g of lithium nickel cobalt manganese aluminum oxide (NCMA, Li[Ni 0.73 Co 0.05 Mn 0.15 Al 0.02 ]O2), 1g of carbon black as a conductive material and 12g of polytetrafluoroethylene (PTFE) as a fluorine-containing binder, and the polytetrafluoroethylene (PTFE) is heat-treated in an air atmosphere by using a furnace at a heat treatment temperature and for a heat treatment time as shown in Table 1 below, and then cooled to room temperature (25°C).
[0183] Performance Evaluation
[0184] The electrode film according to each of Examples 1 to 3 and Comparative Examples 1 to 4 was evaluated as follows.
[0185] (1) Elongation at break (%)
[0186] The elongation at break of each electrode film was measured by using a UTM instrument (ZwickRoell Co.) under the following test conditions.
[0187] Test conditions: ASTM D 638, preload 0.01 kg / cm, test speed 50 mm / min.
[0188] (2) Modulus (MPa)
[0189] The modulus of each electrode film was measured by using a UTM instrument (ZwickRoell Co.) under the following test conditions.
[0190] Test conditions: ASTM D 638, preload 0.01 kg / cm, test speed 50 mm / min.
[0191] (3) Tensile Strength (MPa)
[0192] The tensile strength of each electrode film was measured by using a UTM instrument (ZwickRoell Co.) under the following test conditions.
[0193] Test conditions: ASTM D 638, preload 0.01 kg / cm, test speed 50 mm / min.
[0194] (4) In the following Table 1, based on the physical properties according to the comparative example, increases in the values of the respective physical properties according to the example are shown.
[0195] The increase in each physical property was calculated according to the formula [(physical property according to the example - physical property according to the comparative example) / (physical property according to the comparative example) x 100 (%)].
[0196] [Table 1]
[0197]
[0198] Referring to Table 1, it can be seen that the electrode film obtained by heat-treating the fluorine-containing binder at 290-310°C and mixing the heat-treated fluorine-containing binder with an active material, etc. according to Examples 1-3 shows significantly improved mechanical properties, including elongation at break, modulus and tensile strength, compared to the electrode film according to Comparative Examples 1-3 that does not use heat treatment or does not meet the above-defined heat treatment temperature conditions. In addition, although the electrode film according to Comparative Example 4 meets the condition of elongation at break (7% or more), it includes 12 parts by weight of the fluorine-containing binder based on the total weight of 100 parts by weight of the electrode film. Therefore, in the case of Comparative Example 4, since the content of the fluorine-containing binder does not fall within the range of 0.5-10 parts by weight based on the total weight of 100 parts by weight of the electrode film, the electrode film shows a significantly low tensile strength.
Claims
1. An electrode film, comprising: Active materials and fluorinated binders, The fluorine-containing adhesive comprises a polytetrafluoroethylene (PTFE) adhesive, The active material includes a lithium transition metal oxide, and The content of the fluorine-containing binder is 0.5-10 parts by weight based on 100 parts by weight of the total weight of the electrode film, and The electrode film exhibits an elongation at break of 7% or more.
2. The electrode film according to claim 1, wherein the lithium transition metal oxide comprises lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel - manganese - cobalt oxide, lithium nickel - manganese - cobalt - aluminum oxide, lithium copper oxide, or two or more of them.
3. The electrode film according to claim 2, wherein the lithium nickel - manganese - cobalt - aluminum oxide is represented by the following Chemical Formula 1: [Chemical Formula 1] Li a [Ni b Co c Mn d Al e 1-f M 1 f O2 wherein M l represents Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, S, or two or more of them, 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1, and 0 ≤ f ≤ 0.
1.
4. The electrode film according to claim 3, wherein the lithium nickel - manganese - cobalt - aluminum oxide is represented by the following Chemical Formula 2: [Chemical Formula 2] Li a [Ni b Co c Mn d Al e 1-f O2 wherein 0.8 ≤ a ≤ 1.2, 0.5 ≤ b ≤ 0.99, 0 < c < 0.5, 0 < d < 0.5, 0.01 ≤ e ≤ 0.1 and 0 ≤ f ≤ 0.
1.
5. The electrode film according to claim 1, wherein the electrode film exhibits an elongation at break of more than 7% and a tensile strength of more than 1.4 MPa.
6. The electrode film according to claim 5, wherein the electrode film exhibits an elongation at break of 7.2 - 7.8%, a tensile strength of 1.4 MPa, and a modulus of 38.3 - 40.9 MPa. 7 . The electrode film according to claim 1 , comprising an active material, a fluorine-containing binder, and a conductive material. 8 . The electrode film according to claim 7 , wherein the conductive material comprises activated carbon, graphite, carbon black, Ketjen black, carbon nanotubes, or two or more thereof.
9. The electrode film according to claim 7, wherein the content of the active material is 85-98 parts by weight, the content of the conductive material is 0.5-5 parts by weight, and the content of the fluorine-containing binder is 0.5-10 parts by weight.
10. The electrode film according to claim 1, which is obtained by a dry process.
11. A method for manufacturing the electrode film as defined in claim 1, comprising the steps of: The fluorine-containing adhesive is heat treated at 290-310°C; preparing a mixture comprising an active material and the heat-treated fluorine-containing binder; kneading the mixture at a pressure equal to or higher than ambient pressure at 70-200° C. to prepare a mixture mass; pulverizing the mixture mass to obtain a mixed powder for an electrode; and The electrode mixed powder is introduced between a plurality of rolls and rolled to form an electrode film.
12. The method for producing an electrode film according to claim 11, wherein the step of kneading the mixture to prepare a mixture mass is performed in a kneader at a pressure equal to or higher than ambient pressure.
13. A method for manufacturing an electrode comprising the step of laminating the electrode film as defined in any one of claims 1 to 10 on a current collector.
14. The method for manufacturing an electrode according to claim 13, wherein in the laminating step, the electrode film has a compression ratio of 30-50%.
15. An electrode comprising: Current collector; and The electrode film as defined in any one of claims 1 to 10 is provided on at least one surface of the current collector.
16. The electrode of claim 15, wherein the current collector further comprises a conductive primer layer on at least one surface thereof.
17. A secondary battery comprising: A positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is the electrode as defined in claim 15.
18. An energy storage system comprising the secondary battery as defined in claim 17 as a unit battery.
